The Trend of Using the Same Platform in Distance Learning during the Covid-19 Pandemic - Vania Zulfa; Elmanora Elmanora; Maya Oktaviani (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2022)
This study aims to determine students' tendency to use the same or different platforms in distance learning to create effective and joyful learning. The study was conducted on 119 students from the Department of Family Welfare Education, Universitas Negeri Jakarta, from April to May 2020. The research was conducted using survey methods—data collected through questionnaires and online interviews. Data analyzed descriptively. The results showed that 74 of 119 students preferred using the same platform during learning. The consistent use of platforms makes it easier for students to access so that the student just focus on lecture material.